PENGARUH SENAM DIABETES TERHADAP INDEKS MASSA TUBUH DAN TEKANAN DARAH PADA PENDERITA DIABETES MELLITUS TIPE 2 DI KLINIK TIARA MEDISTRA DESA BANDAR SETIA - ZAKIYAH DARAJAT; FANI ADE IRMA (JURNAL ILMIAH SIMANTEK, 2020)
Diabetes is a multifactorial disease thats every year is an increase in new diabetics, diabetes disrupts the metabolism ofendocrine system and can affect all organs of the body, especially the cardiovascular system. Exercise has an important rolein patients controling blood pressure and weight. Low impact aerobics are sport recomendations for diabetic patients toincrease insulin sensitivity. To determine the effect of diabetes exercise on the patient's body weight which is affect the bodymass index and blood pressure of type 2 diabetes mellitus patients at Tiara medistra clinic-Bandar Setia. This is aquantitative research using Quasi experiments with one group pre and post test. This result of this study used the Shapiro-Wilk normality test. The value of the results of this analysis is 0.013 (p <0.05) in systolic blood pressure, 0.002 (p <0.05) indiastolic blood pressure, and 0.012 (p <0.05) in body mass index. From the results of this study it was concluded thatdiabetes exercise for 30 minutes affected blood pressure and body mass index.